2008
DOI: 10.1161/hypertensionaha.107.098251
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Dietary Potassium Against Vascular Injury in Salt-Sensitive Hypertension

Abstract: Abstract-Hypertensive cardiovascular damage is accelerated by salt loading but counteracted by dietary potassium supplementation. We suggested recently that antioxidant actions of potassium contribute to protection against salt-induced cardiac dysfunction. Therefore, we examined whether potassium supplementation ameliorated cuff-induced vascular injury in salt-sensitive hypertension via suppression of oxidative stress. Four-week-old Dahl salt-sensitive rats were fed a normal-salt (0.3% NaCl), high-salt (8% NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 39 publications
0
64
1
Order By: Relevance
“…6,[20][21][22][23][24] Second, hyperkalemia may occur less frequently in patients with a high salt diet than a low salt diet, because salt loading decreases serum K level. 33 Moreover, animal studies, including our own, 34,35 suggest that a mild increase in serum K level may promote organ protection in relatively K-depleted CKD patients with a high salt intake.…”
Section: Discussionmentioning
confidence: 89%
“…6,[20][21][22][23][24] Second, hyperkalemia may occur less frequently in patients with a high salt diet than a low salt diet, because salt loading decreases serum K level. 33 Moreover, animal studies, including our own, 34,35 suggest that a mild increase in serum K level may promote organ protection in relatively K-depleted CKD patients with a high salt intake.…”
Section: Discussionmentioning
confidence: 89%
“…Superoxide concentrations in renal cortex and outer medulla (2), as well as in vascular tissue (44), are increased with chronic K-restriction. Conversely, a high-K diet reduced ROS production in vascular tissue and protected against deleterious effects of a high Na intake (17). These effects may be mediated in part by angiotensin II (ANG II).…”
Section: Effects Of [Kmentioning
confidence: 99%
“…The renal and cardiovascular protector effects of a potassiumenriched diet have been described in large epidemiological studies (Ascherio et al, 1992;Khaw and Barrett-Connor, 1987;Tobian, 1988), as well as in diverse animal models (Ellis et al, 1992;Jin et al, 1999;Kido et al, 2008;Wang et al, 2005), which have demonstrated that dietary potassium supplementation prevented vascular and renal injury caused by high salt intake. In this cardiovascular protector context, a pivotal role has been assigned to the anti-hypertensive effects of potassium, as well as to other vasoprotective mechanisms, such as the reduced production of reactive oxygen species (Matsui et al, 2006) and the direct inhibition of intimal hyperplasia (Kido et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this cardiovascular protector context, a pivotal role has been assigned to the anti-hypertensive effects of potassium, as well as to other vasoprotective mechanisms, such as the reduced production of reactive oxygen species (Matsui et al, 2006) and the direct inhibition of intimal hyperplasia (Kido et al, 2008). Several authors have described a beneficial effect of potassium on the generation and release of nitric oxide (NO; see Zhou et al, 1999;Zhou et al, 2000) and a restoration of endothelium-dependent vasorelaxation has been shown in diverse hypertensive rat models (Sudhir et al, 1993;Sugimoto et al, 1988;Zhou et al, 1999).…”
Section: Introductionmentioning
confidence: 99%